Everyday security threats : Perceptions, experiences, and consequences - Stevens, Daniel; Vaughan-Williams, Nick (Book collections on Project MUSE., 2016)
Everyday security threats explores public perceptions of security threats in contemporary Britain, using data from extensive fieldwork and drawing on perspectives from International Relations, security studies and political psychology.